The Influence of Foreign States on the Activities of Extremist Organisations in the South of Russia - Anton V. Bredikhin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. The problem of the spread of extremist organizations’ activities in the South of Russia is intensified due to the increasing role of international actors and the influence of neighboring States. Extremist groups are included in the sphere of interests of countries with high level of institutional instability that have unresolved territorial administrative problems and also major terrorist organizations such as the ‘Islamic State’ (ISIL) prohibited on the territory of the Russian Federation.